A rare pediatric neurometabolic disorder: Leigh syndrome - Kumar, Amit; Jasiwal, Sakshi (Indian Journal of Case Reports, 2024)
Subacute necrotizing encephalomyelopathy called Leigh Disease is a rare inherited pediatric neurological disorder generally involving infants. The condition primarily involves the central nervous system and the most involved structures are basal ganglia, thalamus, and brainstem. In this disorder, there is a progressive loss of mental and movement abilities associated with abnormal muscle tones, weakness, visual loss, respiratory failure, and strikingly, we got raised lactate levels in the blood, cerebral spinal fluid, and other body fluids. The prognosis of this condition is bad as there is no effective treatment and finally, the patient succumbs to death mostly due to respiratory failure. Here, we present a case of Leigh disease in an 8-month-old boy having chief complaints of delayed motor (weakness), and cognitive development with a previous history of recurrent respiratory infection. Upon recent radiological imaging, gross neurological abnormalities were seen which suggested the possibility of Leigh disease which was further confirmed by raised body fluid lactate levels.